Study of $B_c^+$ decays to the $K^+K^-π^+$ final state and evidence for the decay $B_c^+→χ_{c0}π^+$ - Collaboratio, L; Aaij, R; Adeva, B; Adinolfi, M; Cheung, S; Evans, T; Gandini, P; Gruberg Cadzon, B; Hadavizadeh, T; Harnew, N; Hill, D; Hussain, N; et al. (American Physical Society, 2016)
A study of $B_c^+→ K^+K^-π^+$ decays is performed for the first time using data corresponding to an integrated luminosity of 3.0 $fb^{-1}$ collected by the LHCb experiment in $pp$ collisions at centre-of-mass energies of $7$ and $8$ TeV. Evidence for the decay $B_c^+→χ_{c0}(→ K^+K^-)π^+$ is reported with a significance of 4.0 standard deviations, resulting in the measurement of $\frac{σ(B_c^+)}{σ(B^+)}×\mathcal{B}(B_c^+→χ_{c0}π^+)$ to be $(9.8^{+3.4}_{-3.0}(stat)± 0.8(syst))× 10^{-6}$. Here $\mathcal{B}$ denotes a branching fraction while $σ(B_c^+)$ and $σ(B^+)$ are the production cross-sections for $B_c^+$ and $B^+$ mesons. An indication of $\bar b c$ weak annihilation is found for the region $m(K^-π^+)<1.834\mathrm{\,Ge\kern -0.1em V\!/}c^2$, with a significance of 2.4 standard deviations.